2021
DOI: 10.3390/w14010039
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Actual Winery Wastewater by Fenton-like Process: Optimization to Improve Organic Removal, Reduce Inorganic Sludge Production and Enhance Co-Treatment at Municipal Wastewater Treatment Facilities

Abstract: Despite many wineries being equipped with onsite wastewater treatment, winery wastewater (WWW) co-treatment at municipal wastewater treatment plants (WWTPs) remains a common practice in wine-making regions. The complex and highly variable nature of WWW can result in negative impacts on WWTP operations, highlighting a need for improved co-treatment methods. In this paper, the feasibility of using the Fenton-like process to pre-treat WWW to enhance co-treatment at municipal WWTPs is assessed. First-stage pre-tre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The homogeneous photo-Fenton process showed a significant removal of TPh, COD, and BOD 5 compared to the heterogeneous photo-Fenton process, most likely due to the rapid availability of iron. In the work of Jorge et al [16], it was observed that the application of a photo-Fenton process increased the removal of turbidity, TSS, TPh, COD, and BOD 5 , similar to the results of this work. The biodegradability was analyzed, with results showing 0.50, 0.85, 0.79, and 0.54, respectively, for the homogeneous photo-Fenton (red and white WW) and heterogeneous photo-Fenton (red and white WW) processes, and thus it can be perceived that both processes enhance the biodegradability of the WW.…”
Section: Discussionsupporting
confidence: 88%
“…The homogeneous photo-Fenton process showed a significant removal of TPh, COD, and BOD 5 compared to the heterogeneous photo-Fenton process, most likely due to the rapid availability of iron. In the work of Jorge et al [16], it was observed that the application of a photo-Fenton process increased the removal of turbidity, TSS, TPh, COD, and BOD 5 , similar to the results of this work. The biodegradability was analyzed, with results showing 0.50, 0.85, 0.79, and 0.54, respectively, for the homogeneous photo-Fenton (red and white WW) and heterogeneous photo-Fenton (red and white WW) processes, and thus it can be perceived that both processes enhance the biodegradability of the WW.…”
Section: Discussionsupporting
confidence: 88%
“…Some organic compounds revel to be recalcitrant and cannot be degraded by biological processes, thus chemical treatments, such as AOPs can be applied. Among the AOPs, we observed the successful application of hydroxyl-based AOPs [23,[25][26][27], sulfate-radicalbased AOPs [28], and ozone-based AOPs [29] in the removal of organic carbon from the WW. The results obtained by these processes showed that the formation of radicals was driven by the application of catalysts (homogeneous and heterogeneous), radiation sources (UV-C, UV-A, ultrasound, and solar), pH, temperature, and COD content.…”
Section: Treatment Processes Wastewater Reuse and Sludge Recyclingmentioning
confidence: 99%